How Emotional Contagion among Teachers Affects the Relationship between Transformational Leadership and Team Cohesion - Giulia Paganin; Lorenzo Avanzi; Dina Guglielmi; Carlos-María Alcover; Greta Mazzetti (Behavioral Sciences, 2023)
Teachers and educators are experiencing turmoil under the drastic changes in educational practices caused by the COVID-19 pandemic. According to research, transformational leaders effectively facilitate organizational change by fostering teachers’ sense of belonging and boosting social identity in their team members, which can result in better team well-being via higher team cohesion. Recently, research has increasingly explored the role of emotional contagion and its relationship with leadership. Accordingly, the current study aims to delve deeper into the role of emotional contagion in linking transformational leadership to cohesion among teachers in the school setting. To this purpose, 581 teachers from northern Italy filled out a self-report questionnaire (72.1% female, Mage = 47.06, and SDage = 11.42). A moderated mediation model was tested to assess the mediating role of organizational identification in the relationship between transformational leadership and team cohesion and how emotional contagion may moderate this association. The obtained results provided support to the hypothesized model. Overall, the present study corroborates the critical role of school principals’ behavior in fostering greater organizational identification among teachers, which is associated with better team cohesion. This study constitutes an early attempt to gain more insight into the role of emotional variables in explaining the influence of leadership behavior.